Simulation of light-illuminated STM measurements - Fukuda, Koichi; Nishizawa, Masayasu; Tada, Tetsuya; Bolotov, Leonid; Suzuki, Kaina; Sato, Shigeo; Arimoto, Hiroshi; Kanayama, Toshihiko (International Conference on Simulation of Semiconductor Processes and Devices, 2014)
A three dimensional simulation system for light-illuminated STM measurements is proposed for the first time combining semiconductor process and device simulators with an FDTD solver. Photo-generation rates estimated from light intensity obtained from the FDTD solver are incorporated into a semiconductor device simulation of a device structure including a semiconductor sample and an STM probe tip. Tunneling currents between the STM probe and the sample are solved consistently with current continuity equations in the semiconductor sample. The usefulness of the proposed method is demonstrated through a case of UV-laser-illuminated STM measurement of a silicon nanowire.